Comparative effects of Nucleostemin silencing in human Molt-4 and Jurkat leukemia T-ALL cells - Rahmati, Marveh; Moosavi, Mohammad Amin; Nourashrafeddin, Seyedmehdi; Hojabri, Zoya; Hasani, Akbar; Zarghami, Nosratollah (Archives of Advances in Biosciences, 2015)
Nucleostemin (NS), a stem cell-abundant nucleolar protein, is critical for maintaining the self-renewal and proliferative properties of normal and cancerous stem cells. Recent data suggests that NS signaling is important for proliferation of T-cells and leukemia cells. This study was conducted to verify the role of NS in pathogenesis and treatment of T-cell acute lymphocytic leukemia (T-ALL). Our results revealed that RNA interference-mediated NS silencing primarily affected clonogenicproperty of T-ALL cells by limiting their self-renewal potential in vitro.These effects were accompanied with inhibition of proliferation and early apoptosis in Jurkat cells (p53-null) while late apoptosis in Molt-4 (p53 functional) T-ALL cells. Collectively, our results suggest that NS is a critical regulator in self-renewal and apoptosis of differentT-ALL cells. This suggests therapeutic potential of this gene in leukemia.